EVALUASI KINERJA JARINGAN IRIGASI DI SALURAN SEKUNDER PADA BERBAGAI TINGKAT PEMBERIAN AIR DI PINTU UKUR - Susi Hariany; Bustomi Rosadi; Nur Arifaini (Rekayasa : Jurnal Ilmiah Fakultas Teknik Universitas Lampung, 2011)
Way Rarem irrigation area is focused on improving the productivity of food crops in Lampung. Servicearea of the Regional Irrigation Way raw Rarem estimated at 22,960 hectares. However, in reality thestandard service area for irrigation area is still not achieved. Based on the issues raised above,needed study to find out the problems occur one is to see the relationship of door opening effect to thethe performance of irrigation networks.The results of research in the field indicate that there has been a difference between the dischargemeasurement results with a standard discharge door opening between 0,025 – 0, 206 m3/sec. Thisindicates that a leak in the secondary channel, causing the discharge was not supposed to be deliveredin accordance with the requirements of the land. Loss water are also performed in the secondarybetween BR 32 to BKR 2 canals and water loss by evaporation to pan evaporation test. The resultsshowed the loss of water channels also occur between 0.009 m 3/sec - 0.025 m3/sec. If calculated on apercentage, then the maximum water loss in the secondary channel is 3,27%. Loss of water due toevaporation in the channel is 0,00108 m3/sec/day. If we calculated the economic impact caused of lossof water in the door, then the loss of water amounting to 0,206 m3/sec will make 1,4574 billion IDR.(One billion four hundred and fifty seven million four hundred thousand rupiahs) for the first time thegrowing season. Thus, needed recalibration of the door in the secondary canal as needed accordancewith the plan so that the irrigation network performance can be improved.